expand:
x(5x-2) -> 5x^2-2x=24x(5x−2)→5x2−2x=24
set equal to 00:
5x^2-2x=24 -> 5x^2-2x-24=05x2−2x=24→5x2−2x−24=0
factorise:
-> 5x^2+10x-12x-24→5x2+10x−12x−24
-> 5x(x+2)-12(x+2)→5x(x+2)−12(x+2)
rArr (x+2)(5x-12)⇒(x+2)(5x−12)
Check to see if correct:
(5x-12)(x+2)=5x^2+10x-12x-24(5x−12)(x+2)=5x2+10x−12x−24
-> 5x^2-2x-24→5x2−2x−24.
set each bracket equal to 00:
5x-12=05x−12=0
-> 5x=12→5x=12
rArr x=12/5⇒x=125
x+2=0x+2=0
rArr x=-2⇒x=−2
Check these values:
2.4(5 xx 2.4-2)=2.4 xx 10=242.4(5×2.4−2)=2.4×10=24
-2(5 xx-2-2)−2(5×−2−2)=-2 xx -12=24#
therefore these values are correct.